Decision Support System Model for Species Selection in Forest Plantations in Malaysia - Kamarudin, Shafinah (2008)

(untitled)
Decision Support System (DSS) is a computer technology that is used to support decision making and problem solving processes. It was first implemented in forestry in early 1980s mainly for temperate forests but few for Malaysian forests. A DSS model for forest plantation in Malaysia is therefore needed because the forest plantation programmes is rapidly taking place. The objectives of this study are to propose a specific DSS model for supporting decision making process in selecting appropriate suitable species based on site conditions and economic parameters, and to develop a prototype based on the initial designed DSS model. In this study, four tree species were used as data samples to develop the model and these are Azadirachta excelsa, Acacia mangium, Hevea brasiliensis and Tectona grandis. An economic module was also incorporated in the model giving users the ability to make predictions on potential cost and benefit margins of the four timber species to be planted. The prototype was developed using Windows platform with Oracle JDeveloper. Java programming language was used to develop this prototype. he development of the prototype follows the initial designed of the DSS model. A survey was also conducted using questionnaire as well as interviews to evaluate the usability of this model. Eight usability factors used in the survey include efficiency, understandability, operability, attractiveness, error prevention, learnability, accuracy and effectiveness. Results from the survey indicated that the user satisfaction index for all usability factors of the DSS model was 0.43. This implies that the respondents were quite satisfied with the model. Furthermore, this study also shows that the factors of understandability, attractiveness and operability of the model have the highest user satisfaction index compared to other usability factors. Results from the interview session reflect some weaknesses of this model and suggestions were given to improve the model. In conclusion, the objectives of this study which are to develop a DSS model and a prototype for Malaysian forest plantation management were achieved. The DSS model is usable to support the decision making process for commercial tree planting in Malaysia. The economic parameters gave new insight on costing and the environmental parameters also complement the DSS model. This study revealed that respondents were quite satisfied with the proposed DSS model. However, additional environmental parameters particularly slope elevation and drainage need to be included. Other tree species and the use of weighing method should also be included to improve the DSS model.